Human Norovirus evolution in a chronically infected host - Doerflinger, Sylvie; Weichert, Stefan; Koromyslova, Anna D.; Schwerk, Christian; Adam, Rüdiger; Hansman, Grant S.; Schroten, Horst (mSphere, 2017)
Typically, human noroviruses cause symptoms of acute gastroenteritis for 2 to 4 days. Often, the virions are shed in stool for several days after the symptoms recede, which in turn can lead to further contamination and transmission. Moreover, a number of reports have considered that chronic norovirus infections, i.e., lasting months and years, might even function as reservoirs for the generation of novel strains that can escape the herd immunity or have modiﬁed binding interactions with histo-blood group antigens (HBGAs). In this study, we analyzed noroviruses isolated from a patient who has presented a chronic infection for more than 6 years. We found that the isolated capsid sequences clustered into two main genetic types (termed A and B), despite a plethora of capsid quasi-sequences. Furthermore, the two genetic types corresponded well with distinct antigenicities. On the other hand, we showed that numerous amino acid substitutions on the capsid surface of genetic types A and B did not alter the HBGA binding proﬁles. However, divergent binding proﬁles for types A and B were observed with human milk oligosaccharides (HMOs), which structurally mimic HBGAs and may act as natural antivirals. Importantly, the isolated capsid sequences only had approximately 90% amino acid identity with other known sequences, which suggested that transmission of these chronic noroviruses could be limited.